NOVEL PULANG KARYA LEILA S. CHUDORI: ANALISIS STRUKTUR PLOT ROBERT STANTON - , EKO SULISTYO, Dr. Pujiharto, M. Hum ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research has a purpose to understand structure of Pulangâs plot. Knowledge about structure of Pulangâs plot use to increase readerâs appreciation. This research use a descriptive method. This method use to analysis of structure Pulangâs plot by getting describe itâs structure, beforehand, then describe itâs aesthetic aspects. This research used structuralisme by Robert Stanton. Robert Stanton emphasize the importance of function in the structure of novel. In Pulangâs plot, description of identity and personal character, description of setting, and conflicts appeared by phas in. Appearance by phas in use to create suspense and surprise. Plot of Pulang has glue and plausible. Glue and plausible use to makes the story like fact. To corroberate itâs main theme, Pulang use dramatic irony (irony of plot).